Polymer Coated CaAl-Layered Double Hydroxide Nanomaterials for Potential Calcium Supplement - Kim, Tae-Hyun (Int J Mol Sci, 2014)
We have successfully prepared layered double hydroxide (LDH) nanomaterials containing calcium and aluminum ions in the framework (CaAl-LDH). The surface of CaAl-LDH was coated with enteric polymer, Eudragit(®)L 100 in order to protect nanomaterials from fast dissolution under gastric condition of pH 1.2. The X-ray diffraction patterns, Fourier transform infrared spectroscopy, scanning electron and transmission electron microscopy revealed that the pristine LDH was well prepared having hydrocalumite structure, and that the polymer effectively coated the surface of LDH without disturbing structure. From thermal analysis, it was determined that only a small amount (less than 1%) of polymer was coated on the LDH surface. Metal dissolution from LDH nanomaterials was significantly reduced upon Eudragit(®)L 100 coating at pH 1.2, 6.8 and 7.4, which simulates gastric, enteric and plasma conditions, respectively, and the dissolution effect was the most suppressed at pH 1.2. The LDH nanomaterials did not exhibit any significant cytotoxicity up to 1000 μg/mL and intracellular calcium concentration significantly increased in LDH-treated human intestinal cells. Pharmacokinetic study demonstrated absorption efficiency of Eudragit(®)L 100 coated LDH following oral administration to rats. Moreover, the LDH nanomaterials did not cause acute toxic effect in vivo. All the results suggest the great potential of CaAl-LDH nanomaterials as a calcium supplement.